Study of the thermo-mechanical and electrical properties of conducting composites containing natural rubber and carbon black - Oliveira, F. A. [UNESP]; Alves, Neri [UNESP]; Giacometti, J. A. [UNESP]; Constantino, C. J L [UNESP]; Job, A. E. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
This work shows the preparation and characterization of composites obtained by mixing natural rubber (NR) and carbon black (CB) in different percentages aiming suitable mechanical properties, processability and electrical conductivity for future applications as transducers in pressure sensors. The composites NR/CB are characterized through dc conductivity, thermal analysis using differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMA), thermogravimetry (TGA) and stress-strain test. The electrical conductivity changed from 10-9 to 10 Sm-1 depending on the percentage of CB in the composite. Besides, it was found a linear (and reversible) dependence of the conductivity on the applied pressure in the range from 0 to 1.6 MPa for the sample 80/20 (NR/CB wt%).
Keywords: Carbon black; Composite materials; Mechanical properties; Mixing; Pressure sensors; Rubber; Stress-strain curves; Thermomechanical treatment; Conducting composites; Pressure range; Stress strain tests; Electric conductivity